Recent Progress in Electrochemiluminescence of Halide Perovskites - Cao, Yue; Zhu, Jun-Jie (Frontiers in Chemistry, 2021)
Halide perovskites are a rapidly developing class of solution-processable semiconductors which, to date, have a huge impact across several scientific communities. The remarkable photophysical attributes of halide perovskites illustrate their considerable potential in the electrochemiluminescence (ECL) realm. Over the past four years, great progress has been achieved in using halide perovskites as ECL emitters. In this mini-review, the basic characteristics, synthetic approaches, and ECL mechanisms for halide perovskite emitters are first introduced. To the best of our knowledge, most of the reported ECL-active halide perovskites and their disclosed unique features are detailly summarized. Stabilization and interface manipulation strategies for desirable ECL performance are further highlighted. The preliminary halide perovskites-related ECL applications are finally discussed, and prospects are also anticipated.